2008
DOI: 10.1007/s11252-008-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction, juvenile survival and retention in an urban fox squirrel population

Abstract: Fox squirrels in an urban environment had an average litter size of 2.83 (95% CI 2.5, 3.16) which was similar to rural populations. Nonetheless, the proportion of squirrels reproductively active during the summer/fall breeding season (0.73) and annually (spring + summer/fall) was higher (1.23) than previously recorded for non-manipulated rural populations. The average monthly survival rate (Ŝ ¼ 0:960) of urban juvenile fox squirrels during the first 14 weeks of life was higher than reported for adult populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The reproductive biology of the fox squirrels we studied did not differ from other populations. McCleery () suggested that urban fox squirrel populations may grow more rapidly than rural ones (McCleery ). Some urban populations in California are expanding rapidly (King , Krause et al ), and have displaced native western gray squirrels in at least 1 urban park (Muchlinski et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproductive biology of the fox squirrels we studied did not differ from other populations. McCleery () suggested that urban fox squirrel populations may grow more rapidly than rural ones (McCleery ). Some urban populations in California are expanding rapidly (King , Krause et al ), and have displaced native western gray squirrels in at least 1 urban park (Muchlinski et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Fox squirrels usually breed twice annually (winter: Nov–Feb with a peak in Dec and Jan; summer: Apr–Jul, with a peak in late Jun; Allen , Brown and Yeager , Moore , Koprowski ), although summer breeding does not always occur (McCloskey and Vohs , Weigl et al ). The proportion of females breeding during a given reproductive season may vary from 0.10 to 0.83 (McCloskey and Vohs , Harnishfeger et al , Hansen and Nixon , Weigl et al , Herkert et al ), but annual proportions in rural populations have exceeded 1.0 because some females reproduce twice per year (e.g., 1.3 in 1 rural population after some females were experimentally removed [Hansen and Nixon ] and 1.2 in an unmanipulated urban population [McCleery ]). Whether these observed high annual proportions are also typical of urban settings is not clear.…”
mentioning
confidence: 99%
“…In polygynous species, a high femalebiased sex ratio in a population dominated by young age classes likely reflects a positive growth rate. For example, in an urban fox squirrel ( Sciurus niger) population with high survival and reproductive rates, the juvenile-to-adult ratio of 0.44 was higher than for rural populations, with all factors combined suggesting that the urban squirrels comprised a source population (McCleery 2009).…”
Section: Age and Sex Structurementioning
confidence: 99%
“…Emigration is likely another important component of population regulation for urban adapter mammals (McCleery 2009;Soulsbury et al 2010). Dispersal appears to be an important density-dependent mechanism in urban foxes (Gosselink 2002;Soulsbury et al 2010), given their highly-structured social systems.…”
Section: Density-dependent Factorsmentioning
confidence: 99%
“…In contrast, some animals can survive and even thrive in cities (Grimm et al, ) and may benefit from increased food availability or reduced predation risk (McKinney, ). In fact, survival, body condition and fecundity are sometimes greater in urban individuals than in rural conspecifics (Lyons, Mastromonaco, Edwards, & Schulte‐Hostedde, ; McCleery, Lopez, Silvy, & Gallant, , McCleery, ). However, given the continuous human disturbance, it remains largely unknown whether urban environments are truly beneficial to some animals or whether they are merely just surviving in these stressful environments (DeStefano & DeGraaf, ).…”
Section: Introductionmentioning
confidence: 99%